KINERJA GURU PASCASERTIFIKASI (Kebijakan Sertifikasi Guru dan Dampaknya Terhadap Kinerja Guru: Studi Kasus pada Madrasah di Kecamatan Darussalam dan Kuta Baro, Kabupaten Aceh Besar) - Rahmat Saleh (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2011)
The Indonesian Government through a Ministry of Culture and Education as well as a Ministry of Religions released a Teacher Certification Program in 2007. One side, the program has responded well to improve the quality of teachers’ prosperity by providing them additional allowance as much as their monthly salary. However, on the other side, several isssues have been arisen in the field which questioning wether the program has met goals well or not. Those issues such as bad practice in preparing portfolios, financial matter and technical aspect in withdrawing a stipend, impact toward teachers’ teaching competency, and including lack of capacity development program after teachers were declared as certified teachers.  This is a qualitative research with approach of public policy analysis. The research focuses on a case study in two sub-disctricts in Aceh Besar by conductiong in-depth interviews with purposed key informants representing the schools and policy makers. The result of this research does not have intention to generalize condition throughout Aceh province but could be a critical findings responding on Teacher Certification Program. Key words: certification program, to improve the quality